Produktitvitas Diatom Perifitik yang Ditumbuhkan pada tipe Subtrat Berbeda Sebagai Alternatif Penyediaan Pakan Alami Udang - Pratiwi, Niken T.M.; Adiwilaga, Enan M.; Widigdo, Bambang; Soedharma, Dedi (Perhimpunan Biologi Indonesia, 2007)
ABSTRACTThe Productivity of Periphytic Diatom Grown on Different Types of Substrates asan Alternative on Providing Natural Feed for shrimp. Providing natural feed is anattempt to support fisheries culture in a polite way for the sustainability of environment.Periphytic community is living aquatic resources that have a potential value for thispurpose. The major component of saline water periphytic community is diatom.The study was emphasized on diatom presentation grown on two types of artificialsubstrates: biocrete (sand, palm fiber, cement) and zeocrete (zeolite, palm fiber, cement).The reseach was conducted in laboratory with an experimen design follows split splitplot in times. The aim of the research is to study the ecological factor and availablenutrients to support the growth of periphitic diatoms (Amphora, Cyclotella, Melosira,Navicula, Phaeodactylum, and Thallassiosira) on two different substrates. Theproductivity of diatom, and the effect of shrimp larvae on the diatom productivity werealso analyzed. Two fertilized materials (biocrete and zeocrete) with two main treatmentsand three levels of treatments each, and unfertilized materials were used as artificialsubstrates for periphitic diatoms. The results show that all treatment could give sufficientbiological available nutrient for the diatoms. The highest diatom productivity was achievedby the population on third level ratio of fertilized biocrete and zeocrete (added by fertilizedwith N:P ratio of 30:l). Diatom productivity follows the shrimp larvae grazing. Theshrimp larvae could grow well on the media with diatom that were grown on fertilizedbiocrete.Key words: periphytic diatoms, natural feed, biocrete, zeocrete, productivity